Gynecomastia: a common indication for mammography in men of all age - Capasso, Raffaella; Sica, A.; D'Amora, M.; Mostardi, Maurizio; Martella, Ilenia; Totaro, Marilina; Della Casa, Giovanni; Vallara, Manuela; Pesce, Antonella; Gatta, G.; Cappabianca, S. (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: Gynecomastia (GM) is the most frequent cause of male breast-related signs and symptoms and represents also the most common indication for mammography (MX) in men. In this article, our 7-year long experience with MX in men suffering from GM is reviewed, and the mammographic features of GM are presented. Methods: MXs performed in male patients at our institution from January 2009 to January 2016 were retrospectively reviewed and patients with mammographic features of GM were selected. Informed consent was waived by the local institutional review board given the retrospective nature of the study. Mammograms were performed in both cranio-caudal (CC) and medio-lateral-oblique (MLO) views according to diagnostic needs. Clinical and pathologic data were obtained by review of patient charts. Results: 37 males (aged between 13-79 years, mean 59 years) referred for MX at our institution because of palpable lump (31/37; 83.8%), breast enlargement (33/37; 89.2%), tenderness or pain (25/37; 67.6%). Of the 37 patients evaluated, 32 (86.5%) had true GM while 5 (13.5%) had pseudoGM. Conclusions: The evaluation of GM can be complex but a stepwise approach that starts with careful history taking and physical examination may obviate the need for extensive work-up. In this context, MX has been shown to be an accurate diagnostic tool for detecting GM and should be the first imaging examination to be performed in all clinically suspicious lesions referred for imaging.